The Greek girl's story - Prévost, abbé, 1697-1763 (The Pennsylvania State University Press, 2014)
"An English translation of the Abbé Prévost's 1740 novel The Greek Girl's Story. Includes foreword by Jean Sgard, notes, and appendices"--Provided by publisher